God as Male–Female: Priscillian, Prophecy, and the Witness of Irenaeus and Marius Victorinus - Mews, Constant J. (Religions, 2024)
This paper examines a comment by Priscillian (d. c. 385) in his Liber apologeticus that certain people erroneously applied to God the unusual Latin neologism, masculofemina. He contrasts their perspective with scriptural teaching about the Holy Spirit being poured out on both men and women. This raises two questions, namely, how Priscillian’s comment relates to accusations he faced of encouraging dangerous intimacy between men and women and the source of his information about their teaching. This paper argues that the central thrust of Priscillian’s teaching is around the notion that the spirit of prophecy was manifested in both sexes, but that he distinguished his teaching from that of Valentinian gnostics to defend his own orthodoxy. It argues that Priscillian acquired this teaching about God as masculofemina from the translation into Latin of the Aduersus haereses of Irenaeus of Lyons (d. c. 202). The term also occurs within the writing of Marius Victorinus (c. 359–61) in defense of Catholic Christianity. Priscillian drew on Irenaeus to defend the orthodoxy of his notion that the gift of prophecy was given to both men and women.